2021
DOI: 10.3389/fimmu.2021.770515
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression Affects Neutrophil Functions: Does Calcineurin-NFAT Signaling Matter?

Abstract: Neutrophils are innate immune cells with important roles in antimicrobial defense. However, impaired or dysregulated neutrophil function can result in host tissue damage, loss of homeostasis, hyperinflammation or pathological immunosuppression. A central link between neutrophil activation and immune outcomes is emerging to be the calcineurin-nuclear factor of activated T cells (NFAT) signaling pathway, which is activated by neutrophil detection of a microbial threat via pattern recognition receptors and result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 105 publications
(142 reference statements)
0
1
0
Order By: Relevance
“…In addition, we have shown that the calcineurin phosphatase (CN)/NFAT transcription factor signaling pathway, a key player in neutrophil activation during the immune responses ( 26 ), is also activated in an IgE-dependent manner ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we have shown that the calcineurin phosphatase (CN)/NFAT transcription factor signaling pathway, a key player in neutrophil activation during the immune responses ( 26 ), is also activated in an IgE-dependent manner ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…Steroids, commonly used to treat autoimmune diseases, signi cantly affect neutrophil recruitment from the bone marrow 14 . In addition, immunosuppressive drugs often reduce the number and function of peripheral neutrophils 15 . Therefore, it is essential to analyze patient samples prior to therapeutic intervention to accurately capture neutrophil behavior.…”
Section: Introductionmentioning
confidence: 99%